Trends and Factors Impacting Healthcare Charges and Length of Stay for Cholecystectomies: A New York State Population-based Analysis - Aria Darbandi; Christina Chopra (University Library System, University of Pittsburgh, 2021)
Background: Gallbladder disease confers a significant economic toll on the United States healthcare system. This study aims to characterize current trends and features of the cholecystectomy population and identify factors that influence the length of stay and total charges. Methods: Case information was extracted for laparoscopic and open cholecystectomies from 2013-2016 using the New York Statewide Planning and Research Cooperative System (SPARCS) database. Descriptive, comparative, and multivariable linear regression analysis was conducted on 58,141 cases assessing age group, race, gender, admission presentation, surgical technique, insurance status, year of operation and severity of illness by the length of stay and total charges. Results: Of all procedures, 91.6% were laparoscopic, and 79.4% were emergent on admission. Total procedures trended down, while laparoscopic and emergent cases steadily increased (p<0.0001). Total charges increased during the study period, while the length of stay decreased (p<0.0001). Open and emergent procedures were associated with a higher cost and longer inpatient stays (p<0.0001). Open procedures were proportionally more common among elderly, male patients, and in elective cases (p<0.0001). Emergent presentation was more common in females, non-whites, and younger patients (p<0.0001). Regression model showed that male gender, open operation, Black race, and emergent presentation were independent predictors for a longer stay and greater total charges (p<0.0001). Medicare insurance predicted lower total charges but longer length of stay (p<0.0001). Conclusion: Race, insurance, procedure type, and patient presentation influence hospital charges and stays following cholecystectomy. Understanding these trends will allow policymakers and providers to limit the healthcare burden of cholecystectomy.